1979
DOI: 10.1111/j.1365-2141.1979.tb01169.x
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Erythrocyte Glutathione Peroxidase Deficiency as a Consequence of Selenium Imbalance during Pregnancy

Abstract: The red blood cell (RBC) glutathione peroxidase (GSH-Px) activity and routine haematological parameters were measured in 38 healthy north Italian full-term pregnant women and in their newborn infants. In 31 pairs the serum selenium concentration was also measured. Data were compared with those of 20 normal adult controls (10 males and 10 females). Newborn infants exhibited significantly lower RBC GSH-Px activity and serum selenium concentrations than adult controls. Pregnant women had serum selenium values int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
10
0

Year Published

1980
1980
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(12 citation statements)
references
References 16 publications
(8 reference statements)
2
10
0
Order By: Relevance
“…Furthermore, increased transfer of oxidized GSH due to membrane damage could be a reason for the decreased intracellular GSH. Some researchers have suggested that increases or decreases in the antioxidant levels occur during normal pregnancy [11,[23][24][25]. As in our study, Carine et al [11] and Zachara et al [24] observed no important difference in the GSH-P levels between pregnant women in the third trimester and nonpregnant women.…”
Section: Discussionsupporting
confidence: 65%
“…Furthermore, increased transfer of oxidized GSH due to membrane damage could be a reason for the decreased intracellular GSH. Some researchers have suggested that increases or decreases in the antioxidant levels occur during normal pregnancy [11,[23][24][25]. As in our study, Carine et al [11] and Zachara et al [24] observed no important difference in the GSH-P levels between pregnant women in the third trimester and nonpregnant women.…”
Section: Discussionsupporting
confidence: 65%
“…Λ good agreement on Superoxide dismutase, catalase and glutathione peroxidase activities in pregnant women does not exist in previously published data (27)(28)(29)35), probably because the blood samples were not obtained at the same period of pregnancy. In the group of mothers we have studied, the blood samples were obtained at the beginning of labour, and the three enzymes were tested on the same sample.…”
Section: Discussionmentioning
confidence: 63%
“…Low activities of glutathione peroxidase in cord blood were previously reported by many authors (22)(23)(24)(25)(26)(27)(28) It is worth mentioning that no correlation was found between the levels of erythrocyte antioxidant enzymatic activities present in cord blood and the levels of bilirubin during the first days of life.…”
Section: Discussionmentioning
confidence: 67%
“…We have found that male newborn erythrocyte Se content is lower than females, and males also have lower plasma and GSHPx activity over the first 2 to 3 weeks of life. Others have also reported that males have lower newborn erythrocyte GSHPx activity 23,45,46 and plasma Se. 46 It is interesting to speculate whether this apparent lower Se status in male infants at birth, particularly as it appears to continue for first 2 to 3 weeks of life, contributes to the clearly higher morbidity and mortality evident in male infants.…”
Section: Discussionmentioning
confidence: 93%